2002
DOI: 10.1161/01.atv.0000012282.39306.64
|View full text |Cite
|
Sign up to set email alerts
|

Long Pentraxin PTX3 Upregulates Tissue Factor Expression in Human Endothelial Cells

Abstract: Abstract-Inflammation is a major contributing factor to atherosclerotic plaque development and ischemic heart disease.PTX3 is a long pentraxin that was recently found to be increased in patients with acute myocardial infarction. Because tissue factor (TF), the in vivo trigger of blood coagulation, plays a dominant role in thrombus formation after plaque rupture, we tested the possibility that PTX3 could modulate TF expression. Human umbilical vein endothelial cells, incubated with endotoxin (lipopolysaccharide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
99
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 146 publications
(107 citation statements)
references
References 36 publications
7
99
1
Order By: Relevance
“…PTX3 specifically enhances LPS-elicited tissue factor activity in vitro, possibly promoting activation of the coagulation cascade in the presence of microbial moieties (49,50). The effect is specific for bacterial endotoxin, since PTX3 does not influence the action of primary proinflammatory cytokines, such as TNF-a and IL-1b.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PTX3 specifically enhances LPS-elicited tissue factor activity in vitro, possibly promoting activation of the coagulation cascade in the presence of microbial moieties (49,50). The effect is specific for bacterial endotoxin, since PTX3 does not influence the action of primary proinflammatory cytokines, such as TNF-a and IL-1b.…”
Section: Discussionmentioning
confidence: 99%
“…These results hint at a possible involvement of PTX3 in thrombotic events associated to sepsis. PTX3 per se does not influence tissue factor expression and activity in monocytes and endothelial cells (49,50), making it unlikely that this is the case in sterile vascular injuries, such as those occurring in acute coronary syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have revealed that, in humans, PTX3 is produced in areas of atherosclerosis and may contribute to the pathogenesis of atherosclerosis 16,33,34) . It has been shown that endothelial cells, macrophages and smooth muscle cells involved in atherosclerosis produce PTX3 16,35) ; therefore, levels of PTX3 may directly indicate the status of vascular inflammation. It has been reported that circulating PTX3 concentrations were higher in patients with heart failure and that these concentrations varied depending on the severity of CVD 13,17,36,37) ; however, it has not yet been confirmed if the levels of circulating PTX3 in obese subjects are higher than in nonobese subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical significance of these different types of human endothelial cells in response to CRP remains to be determined. In addition, CRP also increases tissue factor, cytokines, and another important thrombotic factor secreted from peripheral monocytes [24] and endothelial cells [25]. In our previous studies, we have demonstrated that CRP decreased the expression of thrombomodulin, endothelial protein C receptor, VEGF receptors and neuropilins in human endothelial cells [26,27].…”
Section: Discussionmentioning
confidence: 99%